The mysterious case of the missing crime writer - Ragnar Jónasson, 1976- (Minotaur Books, 2025)
"The next thrilling golden-age-style mystery from #1 Icelandic bestseller Ragnar Jónasson, author of Death at the Sanatorium and Reykjavík. One winter evening, bestselling crime author Elín S. Jónsdóttir goes missing. There are no clues to her disappearance and it is up to young detective Helgi to crack the case before its leaked to the press. As Helgi interviews the people closest to her-a publisher, an accountant, a retired judge-he realizes that Elín's life wasn't what it seemed. In fact, her past is even stranger than the fiction she wrote. As the case of the missing crime writer becomes more mysterious by the hour, Helgi must uncover the secrets of the writer's very unexpected life"-- Provided by publisher.